NOISE LEVEL EVALUATION, ITEMS SECURITY AND ERGONOMIC IN AGRICULTURAL TRACTORS - Baesso, M. M.; Gazzola, M.; Bernardes, S.; Brandelero, E.; Modolo, A. (Revista Brasileira de Engenharia de Biossistemas, 2015)
The levels of noise emission from agricultural machinery, are not immediately apparent, but the cumulative effects over time include hearing loss According the Brazilian Ministry of Labor and Employment (NR 15), A noise level above the maximum allowed for an 8-hour workday, is 85 decibels (dB (A)). This study aims to evaluate the levels of noise emitted by 12 agricultural tractors of different models powers and to compare the results with existing regulations in Brazil. Ergonomic and safety features of the tractors were surveyed and listed as their compliance or not. It was observed that for tractors without enclosed without cab protection noise level close (10 cm) to the ears of operators were higher than the levels allowed by the Regulatory Standard (NR15), requiring the use of hearing protection for operators. In conclusion although the reduction of noise close to the ear of the operator is provided by the presence of closed factory originating booths. In addition it was found that the newest tractors best meet the safety requirements and ergonomics.